Soil Fertility and Maize Residue Quality All Effect the Exogenous Carbon Sequestration Only in the Short Term in Macroaggregates, but Not in Microaggregates - Nan Ma; Liangjie Sun; Yingde Xu; Shuangyi Li; Jiayan Li; Pingluo Xue; Hongbo Yang; Ramona Mörchen; Jingkuan Wang (Agronomy)
Understanding the mechanisms of converting plant residue carbon (C) into soil C is important for managing the soil C pool and improving soil fertility. However, little is known yet about how the heterogeneous C from the plant residues, e.g., from the various plant parts, is bound in the aggregates of soil with different initial fertility. To address this, an incubating experiment was carried out through the addition of the 13C-labelled aboveground (stems and leaves) and belowground (roots) residue of maize into Mollisols with high and low fertility. Soil aggregates (> 250 μm and < 250 μm) were sieved, and their δ13C of soil organic carbon (SOC) was quantified. The amino sugar content (calculating for microbial residue C, MRC) and the contribution of MRC to the SOC pool (MRC/SOC) were calculated. The results showed that the SOC and maize residue-derived carbon (MDC) concentrations decreased quickly at the beginning, and then, the decrease slowed down until reaching a relatively constant level, and the two stages corresponded to two main microbial anabolism processes, which were entailing synthesizing living microbial biomass and producing microbial residues, respectively. During the beginning period, limited priming effects were observed, but this priming effect is stronger in the macroaggregates of high-fertility soil. The study further proved the existing conclusion that soil fertility and maize residue quality both influenced the C sequestration in the short term but not in the long term in macroaggregates. In the microaggregates, however, only maize residue quality influenced the C sequestration in the long term. In addition, the microaggregates exhibited higher MDC and SOC concentration, and reached a steady state for the MRC/SOC dynamics later than the macroaggregates. These indicated that the microaggregates had a larger C sequestrating capacity than the macroaggregates. The results suggest that soil aggregates are a major factor influencing exogenous C sequestration, even regulating the effective duration of soil fertility and plant quality.